2012
DOI: 10.3109/09638288.2012.694574
|View full text |Cite
|
Sign up to set email alerts
|

The meaning and value of taking part in a person-centred arts programme to hospital-based stroke patients: findings from a qualitative study

Abstract: Arts interventions such as the one implemented and evaluated in this study provide a positive and valuable experience for longer staying stroke patients, contributing to their mental well-being during an otherwise distressing illness and hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 31 publications
1
55
0
Order By: Relevance
“…Participants in this study found that engaging in such caring occasions enhances a sense of enjoyment and self-expression, and strengthens selfappreciation, connection with others, and affirmation of life. Our findings are similar to those of previous research findings, that is, creative art-based activities can be used as a caring modality for restoring the sense of harmony between a person's mind and body (Baumann et al, 2013;Beesley et al, 2011;Erci et al, 2003;Rancour & Barrett, 2011). Throughout the LACE, many participants used the art process to create a new personal sense, such as creating a "poststroke" self-portrait, finding meaning to personal struggles, visualizing personal strengths to live with stroke, and connecting with self, others in the environment, life, and nature.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Participants in this study found that engaging in such caring occasions enhances a sense of enjoyment and self-expression, and strengthens selfappreciation, connection with others, and affirmation of life. Our findings are similar to those of previous research findings, that is, creative art-based activities can be used as a caring modality for restoring the sense of harmony between a person's mind and body (Baumann et al, 2013;Beesley et al, 2011;Erci et al, 2003;Rancour & Barrett, 2011). Throughout the LACE, many participants used the art process to create a new personal sense, such as creating a "poststroke" self-portrait, finding meaning to personal struggles, visualizing personal strengths to live with stroke, and connecting with self, others in the environment, life, and nature.…”
Section: Discussionsupporting
confidence: 82%
“…Art-based creative activities have been used as complimentary therapy in rehabilitation as a means for promoting personal expression, intellectual, aesthetic, and social growth, as well as in recognizing and supporting affective concerns, thus improving health and well-being (Malchiodi, 2000). Clinical groups where creative arts have been applied include those with chronic pain (Kelly, Cudney, & Weinert, 2012), stroke (Baumann, Peck, Collins, & Eades, 2013;B€ azner & Hennerici, 2007;Beesley, White, Alston, Sweetapple, & Pollack, 2011;Gonen & Soroker, 2000), Alzheimer's disease (Chancellor, Duncan, & Chatterjee, 2014;Walsh et al, 2011), and cancer (e.g., Ho, 2005;Visser & Hoog, 2008). The value of creative arts in promoting holistic well-being has been gradually recognized in the rehabilitation or recovery from major life-altering illnesses (Kelly et al, 2012;Malchiodi, 2000;Rancour & Barrett, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature suggests that patients in hospitals experience a sense of powerlessness or lack of control over their aesthetic environment. Similarly, further exploration of the role of the curator in hospital would be useful, as this person may play a pivotal role in encouraging participants to continue their aesthetic interests (Lawson and Phir, 2003;Baumann, 2013). 17,18 Hospital Aesthetics…”
Section: Importance Of Arts Interests and Drop In Attendancementioning
confidence: 98%
“…The relationship between self-efficacy and well-being in stroke survivor's stroke is a leading cause of death in the Western world [1], and is the most common disabling disease, having profound and wide-ranging effects on the physical, psychological and social aspects of an individual's life [2][3][4][5][6]. The focus of health care professionals, particularly early in the period following stroke, is on physical functioning in rehabilitation.…”
Section: Introductionmentioning
confidence: 99%